ECOLOGICAL AND ECONOMIC ANALYSIS OF ADAPTIVE LANDSCAPE SYSTEMS UNDER CONDITIONS OF SUSTAINABLE DEVELOPMENT - Abisheva Gulmira Olzhabekovna; Taukenova Lyazat Zhumabaevna; Ismailova Diana Toleubaevna; Sunakbaeva Dilora; Shamuratova Nazgul Balabaevna; Petr Hajek (Academic Journal of Physical and Chemical Sciences, 2020)
The article considers the adaptive-landscape system, which consists of the natural, cultural and historical characteristics of a particular area. The article describes the main characteristics of the territory, landscape elements; the importance and negative or positive expression of each characteristic is determined; The assessment of the spatial conditions of the landscape is given. These indicators formed the basis of the environmental and economic analysis of the territory. A new systematic approach to the landscape, measures to revitalize spring areas, and measures to combat erosion: organizational, agricultural, technical measures are proposed.